Marketing strategies for promoting workplace hepatitis B and C virus testing: a cross-sectional study using correspondence analysis in Japan - Sakai, Kosuke; Nakazawa, Shoko; Fukai, Kota; Furuya, Yuko; Korenaga, Masaaki; Tatemichi, Masayuki (Frontiers in Public Health, 2025)
AimIn this study, we aimed to identify the priority group for promoting the implementation of hepatitis virus testing in Japanese workplaces. To this end, we determined (1) the workplace departments interested in hepatitis virus control, (2) the information required to implement testing, and (3) the most effective communication strategies and social networking services (SNS) for disseminating this information.MethodsWe surveyed 2,000 executives and human resources (HR) personnel from various industries in Japan using an online questionnaire. Respondents were enquired about the information required for hepatitis testing, their use of information media and SNS, and their workplace hepatitis testing practices. Data were analyzed using co-occurrence networks, heat maps, and correspondence analysis to visualize the relationships between workplace positions and information needs, media, and SNS.ResultsEducation, training, and recruitment personnel, but not top managers, expressed strong interest in hepatitis virus testing and required information on medical facilities, communication, prejudice management, and support plans. These groups frequently use three typical Internet sites as information sources for HR. Business owners were less interested in hepatitis control.ConclusionOur findings will contribute to developing social marketing strategies for promoting hepatitis virus control in the workplace. Despite the government’s notice to strengthen measures against viral hepatitis, it may not be receiving enough attention from employers. A possible strategy is to share practical information with education and recruitment staff through HR-focused media. The validation of the effectiveness of this strategy remains warranted.